The Effect Of Gender Diversity and Financial Performance On Stock Returns With Sustainability As An Intervening Variable - Maulana, Yasir; Masruroh, Rina; Komarudin, Munir Nur (Universitas Bangka Belitung, 2024)
Sustainability and return on stock represent crucial factors in a company's development. Board gender diversity and financial performance can influence a company's Sustainability and return on stock. This study employs a quantitative research method analyzing data from 17 companies, utilizing financial reports from 2018 to 2021. The research findings indicate no significant influence of board gender diversity and financial performance on stock return through a company's Sustainability. These findings underscore the complexity of the dynamics between these factors, emphasizing the need for an integrated approach in corporate management to achieve an optimal balance between Sustainability, return on stock, and inclusive business practices.